Modification and Synergistic Studies of a Novel Frog Antimicrobial Peptide against Pseudomonas aeruginosa Biofilms - Xinze Liu; Daning Shi; Shiya Cheng; Xiaoling Chen; Chengbang Ma; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Lei Wang; Mei Zhou (MDPI AG, 2024)
The overuse of traditional antibiotics has resulted in bacterial resistance and seriously compromised the therapeutic efficacy of traditional antibiotics, making the exploration of new antimicrobials particularly important. Several studies have shown that bioactive peptides have become an important source of new antimicrobial drugs due to their broad-spectrum antibacterial action and lack of susceptibility to resistance. In this study, a novel bioactive peptide Nigrosin-6VL was characterised from the skin secretion of the golden cross band frog, Odorrana andersonii, by using the 'shotgun' cloning strategy. Modifications on the Rana Box of Nigrosin-6VL revealed its critical role in antimicrobial functions. The peptide analogue, 2170-2R, designed to preserve the Rana Box structure while enhancing cationicity, exhibited improved therapeutic efficacy, particularly against Gram-negative bacteria, with a therapeutic value of 45.27. Synergistic studies demonstrated that 2170-2R inherits the synergistic antimicrobial activities of the parent peptides and effectively enhances the antimicrobial capacity of cefepime and gentamicin against both planktonic cells and biofilms. Specifically, 2170-2R can synergise effectively with cefepime and gentamicin against different strains of P. aeruginosa biofilms. Consequently, 2170-2R holds promise as a potent antimicrobial agent developed to combat infections induced by Pseudomonas aeruginosa.